1990
DOI: 10.7164/antibiotics.43.1502
|View full text |Cite
|
Sign up to set email alerts
|

Use of resins for trichothecene production in liquid cultures.

Abstract: During the course of studies on the production and isolation of macrocyclic trichothecenes from fungal isolates,l) we have developed procedures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…Two 4-L fermentations of submerged cultures of M. verrucaria (ATCC 24571) were conducted, one with and one without added Amberlite XAD-7 resin. Earlier, we had shown that adding resin to liquid cultures of Myrothecium could sometimes increase the level of trichothecene production, but in the present case, both cultures yielded essentially the same quantities and types of trichothecenes. The combined crude extracts (7.5 g) of the above cultures were processed by a series of chromatographic procedures (see Experimental Section) to yield 400 mg of a 3:1 mixture of roridin E ( 3a ) and isororidin E ( 3b ) and 20 mg each of epiroridin E ( 3c ) and epiisororidin E ( 3d ).…”
Section: Resultscontrasting
confidence: 52%
“…Two 4-L fermentations of submerged cultures of M. verrucaria (ATCC 24571) were conducted, one with and one without added Amberlite XAD-7 resin. Earlier, we had shown that adding resin to liquid cultures of Myrothecium could sometimes increase the level of trichothecene production, but in the present case, both cultures yielded essentially the same quantities and types of trichothecenes. The combined crude extracts (7.5 g) of the above cultures were processed by a series of chromatographic procedures (see Experimental Section) to yield 400 mg of a 3:1 mixture of roridin E ( 3a ) and isororidin E ( 3b ) and 20 mg each of epiroridin E ( 3c ) and epiisororidin E ( 3d ).…”
Section: Resultscontrasting
confidence: 52%
“…We concluded that in the presence of HP20 cercosporamide was efficiently sequestered by the resin, thereby mitigating its self-toxic effect during the course of the fermentation. Adsorbent resins have been in use for some time to mitigate self-toxicity of metabolites produced by many soil bacteria (Table 1), and this technique is also known to increase stability of products during fermentations [2][3][4][5][6][7][8][9][10][11][12][13], but this approach has rarely been used for fungal fermentations [14][15][16].…”
Section: Pdb + 3% Hp20mentioning
confidence: 99%
“…Fermentations are generally performed in media containing an adsorbent resin to mitigate the self-toxicity of the product to the producer and to increase stability of the products excreted during fermentation. Many of the soil streptomyces producing highly toxic secondary metabolites have been fermented in media containing various adsorbent resins [2][3][4][5][6][7][8][9][10][11][12][13], but this approach has rarely been applied to improve secondary metabolite production in fungal fermentations [14][15][16]. Adsorbent resins are widely used for solid-phase extraction, isolation and purification of a wide variety of pharmaceutical products [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Resins XAD-7 and Amberchrom CG-161 captured verrucarin A ( 8 ) and roridin A ( 9 ) more effectively. 181 The production of dynemicin A ( 10 ) by Micromonospora chersina ATCC 53710 was assessed in the presence of HP-20, XAD-2, XAD-7 and XAD-8 resins. 182 Addition of HP-20 increased the production of 10 by 4.5-fold and addition of XAD-8 promoted an increase of 5.2-fold.…”
Section: Facing the Challenges In The Isolation Of Hydrophilic Compoundsmentioning
confidence: 99%
“…583 Flavonoid glycosides are usually mono-and diglycosylated, while tri-and tetraglycosylated avonoids are less common. The tetraglycosylated derivative of kaempferol (181) was isolated from the aqueous extract of the aerial parts of Vigna luteola by chromatography on Si-gel (MeOH in CHCl 3 ), followed by Sephadex LH-20 (MeOH), a second separation on Si-gel under the same conditions and nal purication by C 18 RP HPLC. 584 The tetraglycosylated pseudo-dimeric avonoid 8,8 0000 -methylene-bis(spinacetin-3-O-robinobioside) (182) was isolated from the leaves of Blutaparon portulacoides by chromatography of the H 2 O extract on C 2 RP column chromatography (twice), followed by purication by two chromatographic separations in Sephadex LH-20 (EtOH).…”
Section: Reviewmentioning
confidence: 99%